2021
DOI: 10.1002/ptr.7144
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin and metabolic syndrome: A review

Abstract: Metabolic syndrome (MetS) is a complex of diseases that lead to mortality due to the development of cardiovascular problems. Quercetin, as an important flavonoid, has various properties such as decreasing blood pressure, anti-hyperlipidemia, anti-hyperglycemia, anti-oxidant, antiviral, anticancer, anti-inflammatory, anti-microbial, neuroprotective, and cardio-protective effects. In this review article, we collected original articles from different sources such as Google Scholar, Medline, Scopus, and Pubmed, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(128 citation statements)
references
References 118 publications
2
89
0
Order By: Relevance
“…Quercetin, one of the most distributed bioflavonoids, is widely present in a variety of vegetables and fruits. A growing number of studies have reported beneficial effects for quercetin in cardiovascular disease, cancer, metabolic syndrome, Alzheimer's disease, and nervous system disorders (Ebrahimpour et al, 2020;Hosseini et al, 2021). In the present study, quercetin decreased blood pressure and cardiac hypertrophy, including cardiomyocyte hypertrophy and cardiac fibrosis as revealed by changed left ventricular structure and enhanced collagen I and α-SMA, in vivo.…”
Section: Discussionsupporting
confidence: 59%
“…Quercetin, one of the most distributed bioflavonoids, is widely present in a variety of vegetables and fruits. A growing number of studies have reported beneficial effects for quercetin in cardiovascular disease, cancer, metabolic syndrome, Alzheimer's disease, and nervous system disorders (Ebrahimpour et al, 2020;Hosseini et al, 2021). In the present study, quercetin decreased blood pressure and cardiac hypertrophy, including cardiomyocyte hypertrophy and cardiac fibrosis as revealed by changed left ventricular structure and enhanced collagen I and α-SMA, in vivo.…”
Section: Discussionsupporting
confidence: 59%
“…The more abundant compounds in QB, namely p -hydroxybenzoic acid, quercetin, and rutin (in the EPF) and acids ferulic and sinapic (in the HPF), are dietary polyphenols with potential biological activities. Several appreciable therapeutic roles have been attributed to them for their antioxidant capacity, and they could, hence, confer bread interesting functional properties [ 39 , 40 , 41 , 42 , 43 , 44 ]. Some in vivo studies have examined their potential biological effects.…”
Section: Resultsmentioning
confidence: 99%
“…No studies addressing the effect of this compound on animal or preclinical disease models have been found in literature searches. Many studies in animals and humans that refer to quercetin and rutin show their anticancer, anti-inflammatory, antidiabetic, and anti-degenerative activities, among others (see the reviews on the subject and references therein: [ 39 , 43 , 46 , 47 , 48 , 49 ]). Recently, Lai and Wong [ 50 ] reviewed the interest in the optimization of quercetin-based functional foods and referred to clinical studies that support the health benefits of the oral intake of this flavonoid.…”
Section: Resultsmentioning
confidence: 99%
“…A higher intake of these compounds has been associated with a reduced incidence of oxidative stress-related diseases, such as cardiovascular diseases and cancer [ 13 , 14 , 15 ]. This group comprises over 5000 different compounds [ 16 ]. Despite extensive ongoing research on flavonoids for several decades, much about the mode of action of flavonoids is still unknown.…”
Section: The Dual Nature Of Oxygen and Antioxidantsmentioning
confidence: 99%